Sintering activation of 316L powder using a liquid phase forming powder - Nattaya Tosangthum (Songklanakarin Journal of Science and Technology (SJST), 2010)
It was found that the addition of a liquid forming powder (up to 6 wt.% of a gas-atomized tin powder) to 316L powdercould activate the sintering process. Sintering activation could be observed by an increase of the sintered density and selected mechanical properties. When optimized tin powder content was used, shorter sintering time and lower sintering temperaturecould produce sintered 316L+tin materials with excellent mechanical properties. Electron dispersive spectroscopy analyses across 316L-tin-316L grains indicated that Ni transportation during the sintering process was enhanced by the presence of liquid tin.